The Legal Perspective of Accepting Donations from Mobile Legends Streamers Affiliated with Online Gambling Sites: Yusuf Qardhawi's Viewpoint - Mahdali Shofi; Tetty MarlinaTarigan (Journal Equity of Law and Governance, 2024)
The rise of Mobile Legends as a popular game has led to new forms of interaction between streamers and their audiences, including financial support through donations. This study examines the legal implications of accepting donations from Mobile Legends streamers affiliated with online gambling sites, using Yusuf Qardhawi’s Islamic legal perspective as a framework. It is not uncommon for viewers to show their appreciation to Mobile Legends streamers as a form of support for the players. However, the issue arises with donations or contributions affiliated with online gambling sites. Streamers, who typically conduct live broadcasts to play Mobile Legends and interact with viewers, have come under scrutiny after receiving donations ranging from tens to hundreds of millions of rupiah from online gambling sites. This study aims to understand the legal perspective of accepting donations from Mobile Legends streamers affiliated with online gambling sites according to Yusuf Qardhawi's viewpoint. This research employs empirical legal research with a qualitative approach. Data is sourced from primary and secondary legal materials. Based on the findings, it is concluded that accepting donations is a permissible act. However, before practicing it, the source must be identified to determine whether it is obtained through lawful means or otherwise. In Islam, gambling is clearly prohibited. A Muslim should not use gambling as a means of entertainment or to fill leisure time, nor is it permissible to use it as a way to earn money under any circumstances.